QUALITY PARAMETERS OF IRRIGATION WATER IN SOME MINOR LIFT IRRIGATION SCHEMES AND THEIR IMPACT ON PHYSICO-CHEMICAL PROPERTIES AND NUTRIENT STATUS OF SOILS - SHARMA, M.P.; BHARTI, V.; PRABHAKARA, J. (Annals of Agricultural Research, 2014)
Due to increasing demand of water for various purposes, use of poor quality water for Â  irrigation and consequently its judicious management, becomes inevitable in certain regions. Sometimes poor quality water is the only available source for irrigation. There are twelve minor lift irrigation schemes in operation in the fringe areas of Ranvir canal command, south of Jammu city, some of them on perennial nallahs which are fed partly by municipal waste water or industrial effluents and partly by seepage/ drainage from higher elevation and some of them on distributaries of Ranvir canal, catering to irrigation needs of agricultural land of 35 to 100 ha of each for the past two decades. Though,irrigation needs of agriculture originally help to harvest bumper crop, it increases soil salinity and has other deleterious effect on soil characteristics. There is a general decline in crop yield under aforesaid minor lift irrigation schemes. In view of this, present investigation was undertaken.